Optoelectronic array of photodiodes integrated with RRAMs for energy-efficient in-sensor computing - Wen Pan; Lai Wang; Jianshi Tang; Heyi Huang; Zhibiao Hao; Changzheng Sun; Bing Xiong; Jian Wang; Yanjun Han; Hongtao Li; Lin Gan; Yi Luo (Light: Science & Applications)
Abstract The rapid development of internet of things (IoT) urgently needs edge miniaturized computing devices with high efficiency and low-power consumption. In-sensor computing has emerged as a promising technology to enable in-situ data processing within the sensor array. Here, we report an optoelectronic array for in-sensor computing by integrating photodiodes (PDs) with resistive random-access memories (RRAMs). The PD-RRAM unit cell exhibits reconfigurable optoelectronic output and photo-responsivity by programming RRAMs into different resistance states. Furthermore, a 3 × 3 PD-RRAM array is fabricated to demonstrate optical image recognition, achieving a universal architecture with ultralow latency and low power consumption. This study highlights the great potential of the PD-RRAM optoelectronic array as an energy-efficient in-sensor computing primitive for future IoT applications.